Preliminary Experience with Small Animal SPECT Imaging on Clinical Gamma Cameras. (14th May 2014) - Aguiar, P.; Silva-Rodríguez, J.; Herranz, M.; Ruibal, A.
Abstract : The traditional lack of techniques suitable for in vivo imaging has induced a great interest in molecular imaging for preclinical research. Nevertheless, its use spreads slowly due to the difficulties in justifying the high cost of the current dedicated preclinical scanners. An alternative for lowering the costs is to repurpose old clinical gamma cameras to be used for preclinical imaging. In this paper we assess the performance of a portable device, that is, working coupled to a single-head clinical gamma camera, and we present our preliminary experience in several small animal applications. Our findings, based on phantom experiments and animal studies, provided an image quality, in terms of contrast-noise trade-off, comparable to dedicated preclinical pinhole-based scanners. We feel that our portable device offers an opportunity for recycling the widespread availability of clinical gamma cameras in nuclear medicine departments to be used in small animal SPECT imaging and we hope that it can contribute to spreading the use of preclinical imaging within institutions on tight budgets.